Complications of Common Gynecologic Surgeries among HIV-Infected Women in the United States - Ana Penman-Aguilar; Maura K. Whiteman; Shanna Cox; Samuel F. Posner; Susan F. Meikle; Athena P. Kourtis; Denise J. Jamieson (Hindawi Limited, 2012)
Objective. To compare frequencies of complications among HIV-infected and-uninfected women undergoing common gynecological surgical procedures in inpatient settings. Methods. We used 1994-2007 data from the Nationwide Inpatient Sample of the Healthcare Cost and Utilization Project, a nationally representative sample of inpatient hospitalizations. Our analysis included discharge records of women aged ≥15 undergoing hysterectomy, oophorectomy, salpingectomy for ectopic pregnancy, bilateral tubal sterilization, or dilation and curettage. Associations between HIV infection status and surgical complications were evaluated in multivariable logistic regression models, adjusting for key covariates. Results. For each surgery, HIV infection was associated with experiencing ≥1 complication. Adjusted ORs ranged from 2.0 (95% confidence interval (CI): 1.7, 2.2) for hysterectomy with oophorectomy to 3.1 (95% CI: 2.4, 4.0) for bilateral tubal sterilization with no comorbidity present. HIV infection was positively associated with extended length of stay and infectious complications of all of the surgeries examined. For some surgeries, it was positively associated with transfusion and anemia due to acute blood loss. Among HIV-infected women, the odds of infectious and other complications did not decrease between 1994-2000 and 2001-2007. Conclusion. HIV infection was associated with elevated frequencies of complications of gynecologic surgeries in the US, even in the era of HAART.